Abdominal Aortic Aneurysm Formation with a Focus on Vascular Smooth Muscle Cells - Guoqing Qian; Oluwaseun Adeyanju; Ayobami Olajuyin; Xia Guo (Life, 2022)
Abdominal aortic aneurysm (AAA) is a lethal degenerative vascular disease that affects, mostly, the elder population, with a high mortality rate (>80%) upon rupture. It features a dilation of the aortic diameter to larger than 30 mm or more than 50%. Diverse pathological processes are involved in the development of AAA, including aortic wall inflammation, elastin breakdown, oxidative stress, smooth muscle cell (SMC) phenotypic switching and dysfunction, and extracellular matrix degradation. With open surgery being the only therapeutic option up to date, the lack of pharmaceutical treatment approach calls for identifying novel and effective targets and further understanding the pathological process of AAA. Both lifestyle and genetic predisposition have an important role in increasing the risk of AAA. Several cell types are closely related to the pathogenesis of AAA. Among them, vascular SMCs (VSMCs) are gaining much attention as a critical contributor for AAA initiation and/or progression. In this review, we summarize what is known about AAA, including the risk factors, the pathophysiology, and the established animal models of AAA. In particular, we focus on the VSMC phenotypic switching and dysfunction in AAA formation. Further understanding the regulation of VSMC phenotypic changes may provide novel therapeutic targets for the treatment or prevention of AAA.